SISTEM PENDIDIKAN HINDU DALAM KITAB SUCI - Made Awanita (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2014)
This article aims to understand the education system according to Hindu teachings contained in the Vedic scriptures. The methods used in the research is a way of recording a document (document recording). While the review steps using literature study methods and descriptive methods. Literature review method is a method used to solve the problem by reading the books or literature support. While the descriptive method is a method of research conducted to describe the events that took place and then the data is systematically arranged in order to obtain a general conclusion. The results of data analysis showed that the education system is contained in the teachings of Catur Asrama (Brahmacari, Grahastha, Wanaprastha and Bhiksuka), which in its implementation has a very close relationship with Catur Purusartha elements, as the four goals of human life, and embraced the concept of lifelong education. Gurukula education model, the Ashram system build moral values and spiritual, disciplined, and obey the regulations studied. Educational concepts expressed in many Hindu scriptures like Vedas, Bhagavadgita, Sarasamuscaya, Kakawin Nitisastra, and Slokantara. Children's education expressed in the Vedic scriptures emphasize on improving the quality of child suputra. Suputra child character, in addition to intelligent, knowledgeable, and have extensive knowledge, also has a noble character, sadhu and virtuous, and able to apply science and religion into itself in a balanced way, as well as the priamacy of human resources can be a professionalism.